2021
DOI: 10.1038/s41598-021-81065-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of cyst fluids improves the diagnostic accuracy of pre-operative assessment of pancreatic cystic lesions

Abstract: Pancreatic cystic lesions (PCL) are increasingly diagnosed. Endoscopic ultrasound fine-needle aspiration (EUS-FNA) cytology is often used for diagnostic confirmation but can be inconclusive. In this study, the role of molecular analyses in the pre-operative diagnostics of PCL is evaluated. Targeted Next Generation Sequencing (NGS) applied on cytology smears was retrospectively evaluated in a cohort of 37 resected PCL. Usefulness of NGS on fresh cyst fluids was tested in a prospective cohort of patients with ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…However, the diagnostic sensitivity in detecting high-grade cysts that should immediately undergo resection, remains relatively low (77%). [12] A valid approach to improve the diagnostic sensitivity of high-grade mucinous lesions, enabling a quick diagnostic statement, is to tackle several biomarkers simultaneously. Relevantly they should all be detected with the lowest possible limit-of-detection [13] as they are not present in a normal cell population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the diagnostic sensitivity in detecting high-grade cysts that should immediately undergo resection, remains relatively low (77%). [12] A valid approach to improve the diagnostic sensitivity of high-grade mucinous lesions, enabling a quick diagnostic statement, is to tackle several biomarkers simultaneously. Relevantly they should all be detected with the lowest possible limit-of-detection [13] as they are not present in a normal cell population.…”
Section: Introductionmentioning
confidence: 99%
“…However, the diagnostic sensitivity in detecting high‐grade cysts that should immediately undergo resection, remains relatively low (77%). [ 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…Recently, molecular and liquid sample analysis has been reported to improve the diagnostic yield of mucinous pancreatic cysts with potentially high-grade lesions, however, the experience with these tests is still limited, as they are not easily available at every center, are time consuming, and require resources [ 24 ]. Whereas use of the string sign is a simple, bedside, cost-free test providing an immediate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“… 93 , 94 Additional mutations ( TP53 , SMAD4 , PIK3CA , PTEN , CDKN2A ) have been shown to be associated with preoperative risks for advanced neoplasia in mucinous cysts, but need validation in multicenter studies. 93 , 95 98 …”
Section: Guidelinesmentioning
confidence: 99%
“…93,94 Additional mutations (TP53, SMAD4, PIK3CA, PTEN, CDKN2A) have been shown to be associated with preoperative risks for advanced neoplasia in mucinous cysts, but need validation in multicenter studies. 93,[95][96][97][98] Cyst fluid glucose level: Multiple studies have shown glucose levels to be lower in mucinous compared with non-mucinous PCNs. 24,99,100 For example, a meta-analysis of eight studies including 609 PCNs found that when PCN fluid glucose was compared with PCN fluid CEA, glucose had a higher sensitivity (91% versus 56%) and diagnostic accuracy for detecting mucinous lesions (94% versus 85%), with no difference in specificity between the tests.…”
Section: Next-generation Sequencing Of Pcn Fluidmentioning
confidence: 99%